Risk-averse procurement strategy under large-scale promotion online considering strategic customer. (October 2017) - Shu, Lei; Wu, Feng; Chu, Lap Keung
Highlights: A pulsed demand model is proposed considering strategic customer behaviour. A risk-averse procurement model is developed in the framework of expected utility. The retailer procures only if the initial inventory level is below a threshold. Risk-averse procurement strategy effectively mitigates risk losing a little profit. It is more significant when the strategic customer ratio becomes larger. Abstract: Driven by large-scale promotion online, customers are becoming strategic in their purchasing behaviour, thus giving rise to pulsed demand. However, pulsed demand is dynamic and highly uncertain. It will not only undermine retailers' profit but will also increase their risks. Based on strategic customer behaviour and multiplicative demand, this paper proposes a pulsed demand model and establishes a procurement decision model within the expected utility framework from the perspective of a risk-averse retailer. A strategic customer ratio (SCR) is employed to denote the proportion of such customers in the entire customer population. We find that the optimal procurement strategy depends on a threshold - a retailer will procure only if the initial inventory level is below this threshold. When the SCR is price-independent, the procurement volume in the promotion period decreases in the selling price, and increases in the SCR in a previous period. When the SCR is price-dependent, the impact of the price in a previous period on the current procurement volume depends on the relationship of price elasticity between SCR and demand in that period. Our numerical study shows that the risk-averse procurement strategy can effectively mitigate risk without significant profit loss, and more so when the SCR becomes larger.